186k views
1 vote
Use a recursive function for the geometric sequence 2, -6, 18, -54,... to represent the 9th term.

f(9) = f(8) • (-3)

f(9) = f(1) • (-3)^8

f(9) = f(1) + -3(8)

f(9) = f(8) + -3(8)​

User Daylerees
by
5.4k points

2 Answers

4 votes

Answer:

The Answer is A. f(9) = f(8) • (−3)

Hope This Helps!

User Giampaolo
by
5.9k points
7 votes

Answer:

f(9) = f(8)·(-3)

Explanation:

A recursive function is one where each successive term is calculated using the previous term;

The clear pattern demonstrated in the sequence of terms shown is that each term is multiplied by -3 to give the next one;

Hence, the correct option is the first.

User Halim Bezek
by
5.5k points